(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2014)
Lipid based drug delivery systems have been examined in various studies and exhibited their potential in controlled and targeted drug delivery. Pharmacosomes, a novel vesicular drug delivery system, offering a unique advantage over liposomes and niosomes, and serve as potential alternative to these conventional vesicles. They constitute an amphiphilic phospholipid complex with drug bearing an active hydrogen atom covalently that bind to phospholipids. They provide an efficient delivery of drug required at the site of action, which ultimately reduces the drug toxicity with reduced adverse effects and also reduces the cost of therapy by imparting better biopharmaceutical properties to the drug, resulting in increases bioavailability, especially in case of poorly soluble drugs. As the system is formed by binding the drug (pharmakon) to carrier (soma), they are termed as pharmacosomes. Depending upon the chemical structure of the drug lipid complex they may exist as ultrafine vesicular, micellar and hexagonal aggregate. Drug having active hydrogen group such as carboxyl, hydroxyl group can be esterified to lipids, resulting in amphiphilic compound. Pharmacosomes are widely used as carriers for various non-steroidal anti-inflammatory drugs, proteins, cardiovascular and antineoplastic drugs. The release of drug from pharmacosomes is generally governed by the process of enzymatic reaction and acid hydrolysis. Here, in the present review paper we have discussed the potential of pharmacosomes as a controlled and targeted drug delivery system and highlighted the method of preparation and characterization.